Pencegahan Kekerasan di Lingkungan Sekolah: Kampanye Edukasi Hukum Mengenai Perlindungan anak dari Kekerasan pada Siswa SMK/SMA di Samarinda - Asyari, Fatimah; Isnawati; K Pasaribu, Benhard; Iwan, Iwan (Pusat Pengembangan Pendidikan dan Bakat Indonesia/Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
Adolescents are a vulnerable group who are highly at risk of experiencing various forms of violence, particularly sexual violence that often occurs within close environments such as families, schools, and social communities. This community service program aimed to enhance students’ legal awareness and knowledge regarding the prevention of sexual violence in schools through a legal education campaign at SMKN 20 Samarinda. The program was conducted over six months, involving 40 participants consisting of student council members, flag-raising troop members, and class representatives from grade XI. The implementation employed a participatory-educative approach, combining legal counseling, interactive lectures, group discussions, and experience-sharing sessions. The activities were carried out in two stages: the first focused on socialization and education about the forms and impacts of sexual violence, while the second involved expert legal speakers who provided in-depth understanding of legal protection and reporting mechanisms. The results showed an improvement in students’ comprehension of sexual violence concepts, their awareness of self-protection rights, and their courage to report incidents of violence occurring in their surroundings. Moreover, the program fostered empathy and social concern among students to build a safe and violence-free school environment. This initiative is expected to serve as an initial step in developing a culture of legal awareness and child protection within educational settings and as a preventive model that can be replicated in other schools.